ADAPTIVE DIVERGENCE IN DARWIN'S RACE: HOW COEVOLUTION CAN GENERATE TRAIT DIVERSITY IN A POLLINATION SYSTEM. (5th November 2012) - Zhang, Feng; Hui, Cang; Pauw, Anton
<x xml:space="preserve">Abstract</x> Understanding how reciprocal selection shapes interacting species in Darwin's coevolutionary race is a captivating pursuit in evolutionary ecology. Coevolving traits can potentially display following three patterns: (1) geographical variation in matched traits, (2) bias in trait matching, and (3) bimodal distribution of a trait in certain populations. Based on the framework of adaptive dynamics, we present an evolutionary model for a coevolving pollination system involving the long‐proboscid fly (Moegistorhynchus longirostris) and the long‐tubed iris (Lapeirousia anceps). The model successfully demonstrates that Darwin's hypothesis can lead to all three patterns if costs are involved. Geographical variation in matched traits could be driven by geographical variation in environmental factors that affect the cost rate of trait escalation. Unequal benefits derived from the interaction by the fly and the flower could potentially cause the bias in trait matching of the system. Different cost rates to trait elongation incurred by the two species and weak assortative interactions in the coevolutionary race can drive divergent selection (i.e., an evolutionary branching) that leads to the bimodal distribution of traits. Overall, the model highlights the importance of assortative interactions and the balance of costs incurred by coevolving species as factors determining the eventual phenotypic outcome of coevolutionary interactions.